West Africa’s dependency on imports of dairy products - (:unkn) unknown (My University, 2024)
The world dairy sector is undergoing sustained development due to the increasing dairy needs of a growing population and a gradual change in diets. This article looks at the place of West African countries in the "dairy planet". The analysis uses FAO statistical data over a long period (1961 to 2017) and customs statistics from 2000 to 2018 for global data ("BACI" database) and from 2000 to 2019 for European data ("COMEXT" database). Although per capita consumption of dairy products per year is still low in many West African countries compared with industrialised countries, overall requirements for dairy products are increasing rapidly as a result of population growth. Due to numerous difficulties (climate, soil quality, low animal productivity, lack of investment, etc.), the development of milk production in West Africa (5.8 billion litres in 2017 for sixteen countries, equivalent to the production of Brittany) is not sufficient to meet local needs. A little over two thirds of the dairy products imported into this zone come from the EU, whose exports have increased sharply over the past ten years (end of milk quotas). Around 40% of these imports are skimmed milk and vegetable fat powder blends (based on palm oil), a product that benefits from a competitive price and which is only very slightly taxed on entry into West African countries.
Keywords: African Research